First myocardial infarction in patients under 60 years old: the role of exercise tests and symptoms in deciding whom to catheterise. Issue 5 (November 1993) - Cross, S J; Lee, H S; Kenmure, A; Walton, S; Jennings, K
Abstract : OBJECTIVE--To determine the role of exercise tests and assessment of angina in the detection of potentially threatening disease in young patients with infarcts. DESIGN--Elective readmission of patients at a mean (SD) of 60 (30) days after acute myocardial infarction for assessment of angina, treadmill exercise tests, and cardiac catheterisation. SETTING--Cardiology department of a teaching hospital. PATIENTS--186 consecutive survivors, aged under 60 years and discharged from the coronary care unit after a first myocardial infarction. MAIN OUTCOME MEASURES--Coronary arteriography, presence of angina, result of exercise tests, and referral for revascularisation. RESULTS--31% of patients had either two vessel disease (with proximal left anterior descending involvement), three vessel disease, or left main stem disease. 49% of all patients had angina. Of the 173 patients who had an exercise test 34% had 1 mm and 24% had 2 mm of exercise induced ST depression. Thirty percent had no angina and a negative exercise test: after a mean (SD) follow up of 16 (4) months none of this symptom free sub-group had died, had experienced a further myocardial infarction, or had been referred for revascularisation. 79% of patients with either two vessel disease (with proximal left anterior descending involvement), three vessel disease, or left main stem disease had either angina or a 1 mm ST depression during the exercise test. CONCLUSION--Patients without cardiac pain after myocardial infarction and without ST changes during an exercise do not need arteriography.